Natural Science Learning System through Mobile Navigation System in Android (NSLS) - Chan, Kok Hoong (Universiti Malaysia Sarawak (UNIMAS), 2014)
Many students faced difficulties in learning natural science subjects such as biology, plant taxonomy and plant science where they are required to recognize plant species. This paper will propose an Android mobile application to aid students in plant recognition with three simple steps: find a plant, take a picture of its leaf and view the results of recognition. The proposed system will provide a platform that not only helps students in identifying plants but also improve their interest in learning about plants. It also helps researchers and botanists with plant monitoring and sample collection using the navigation feature. The aim of this project is to develop an Android mobile application by implementing image processing technique using OpenCV image processing library and provide fairly accurate results. - image processing, navigation, plant recognition, Android